Spontaneous uterine rupture during pregnancy after laparoscopic myomectomy – case report - Jakub Młodawski; Aleksandra Bielak; Marta Młodawska; Grzegorz Świercz (Problemy Pielęgniarstwa, 2023)
Herein we describe a case of spontaneous uterine rupture at 35 weeks of pregnancy in a 37-year-old female patient in her first preg-nancy after in vitro fertilization, who had had a myomectomy 7 years earlier. The indication for the procedure was a myoma partially penetrating the uterine cavity (FIGO classification group 2-5) causing abnormal uterine bleeding. The myomectomy was performed by laparoscopy with layered suturing of the tumour bed. The patient came to the Obstetrics and Gynaecology Clinic due to increasing abdominal pain. Additional examinations revealed tenderness of the uterus, foetal tachycardia, and the presence of free fluid in the Douglas pouch during ultrasound examination. An urgent caesarean section was done, during which a full-walled uterine rupture was visualized at the fundus at the site of the tumour enucleation. Conservative treatment was chosen, leaving the uterus in place. The uterine muscle was sutured in layers. The postoperative period was uneventful. The patient was discharged home in good gen-eral condition.